2011
DOI: 10.1590/s1516-35982011000800018
|View full text |Cite
|
Sign up to set email alerts
|

Feather and blood meal in pre-starter and starter diets for broilers

Abstract: -Two experiments were carried out (pre-starter and starter phases) to evaluate the effect of feather and blood meal on performance, organ development and digestibility and retention of nutrients in broilers. In the first experiment, it was used 280 birds and in experiment 2, it was used 240 birds. The experimental diets were formulated with four levels of feather and blood meal (0%, 2%, 4% and 6%) all of them isonutritive and isoenergetic. A metabolic assay was developed on the 4 th and 7 th days of age in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…The inclusion of FBM did not determine a reduction in performance variables in any of the studied processing methods. These results are similar to those found by Xavier et al (2011), who evaluated increasing levels (0, 2, 4, and 6%) of FBM in the broiler starter diet and observed no effects on weight gain, feed intake, or feed conversion. Nevertheless, the diet with FBM turned out to be economic, as it increased nutrient and energy diversity in poultry diets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The inclusion of FBM did not determine a reduction in performance variables in any of the studied processing methods. These results are similar to those found by Xavier et al (2011), who evaluated increasing levels (0, 2, 4, and 6%) of FBM in the broiler starter diet and observed no effects on weight gain, feed intake, or feed conversion. Nevertheless, the diet with FBM turned out to be economic, as it increased nutrient and energy diversity in poultry diets.…”
Section: Discussionsupporting
confidence: 90%
“…In experiments conducted with the same ingredient evaluated in this experiment, Xavier et al (2011) observed that the inclusion level of 6.0% in broiler pre-starter diet worsened performance up to 21 days of age, eliciting a negative linear response from weight gain and feed intake, but no changes in feed conversion. The authors recommended the inclusion of 3 to 4% in the broiler pre-starter and starter phases.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The lower feed intake observed in quails fed with highest levels of FM justify the results observed for the weight gain. Several researchers have indicated a maximum limit of 4% inclusion of FM without any loss of performance (XAVIER et al, 2011;ROSTAGNO et al, 2011). However, Holanda et al (2009) evaluated increasing levels of FM inclusion in diets for broiler chickens, aged seven to 42 days, and concluded that up to 8% may be employed without any loss in production.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of feather meal (FM) in poultry diets reduces costs without negatively affecting performance. It also increases abattoirs' profits, especially for poultry integration, offering low costs in food production and poultry diet and a decrease in environmental pollution (BELLAVER et al, 2005;XAVIER et al, 2011;KHOSRAVINIA et al, 2015). Hydrolyzed FM is produced by cooking nondegraded feathers, obtained during the slaughter of poultry, under pressure.…”
Section: Introductionmentioning
confidence: 99%